2014
DOI: 10.1186/1471-2105-15-s6-s3
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven discovery of seasonally linked diseases from an Electronic Health Records system

Abstract: BackgroundPatterns of disease incidence can identify new risk factors for the disease or provide insight into the etiology. For example, allergies and infectious diseases have been shown to follow periodic temporal patterns due to seasonal changes in environmental or infectious agents. Previous work searching for seasonal or other temporal patterns in disease diagnosis rates has been limited both in the scope of the diseases examined and in the ability to distinguish unexpected seasonal patterns. Electronic He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…While summary review of previous single disease studies may suggest that utilization rates tend to peak in the winter, our analysis of temporal variation in a diverse collection of clinical conditions has shown that summer peaks predominate. Furthermore, previous work has provided only a narrow understanding of temporal variation in hospital utilization whereas the largest study we identified was limited to only the top one-fifth of conditions with the largest mean monthly admission rate [15]. Here, we have dramatically expanded understanding of temporal variation through the study of 246 condition-specific hospital utilization rates, which together encompass nearly all medical conditions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While summary review of previous single disease studies may suggest that utilization rates tend to peak in the winter, our analysis of temporal variation in a diverse collection of clinical conditions has shown that summer peaks predominate. Furthermore, previous work has provided only a narrow understanding of temporal variation in hospital utilization whereas the largest study we identified was limited to only the top one-fifth of conditions with the largest mean monthly admission rate [15]. Here, we have dramatically expanded understanding of temporal variation through the study of 246 condition-specific hospital utilization rates, which together encompass nearly all medical conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Such traditional approaches are unlikely to uncover unexpected temporal patterns that may be revealed only by broad data mining techniques applied across many conditions. While one previous study utilized a data mining approach, it was limited to the analysis of only one-fifth of diseases with the highest admission rates at a single institution, leaving the majority of diseases across a broader population unstudied [15]. In addition, past studies have reduced the complexity of temporal pattern analysis to three simple indices, namely amplitude, period, and phase, which together provide only a limited characterization of temporal variation.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonality was identified by estimating the power spectral density contained in the estimated incidence time-series data for each pathogen separately. Specifically, we utilize the Lomb-Scargle periodogram [2426] to identify the spectral power for each resolvable frequency, which is constrained by the temporal length of GEMS and our two-week sampling interval. The Lomb-Scargle periodogram is especially useful for analyzing constrained time-series; the technique quantifies the uncertainty of detecting a specific periodicity [27] even with unevenly sampled data [25].…”
Section: Methodsmentioning
confidence: 99%
“…While syndromic surveillance typically focuses on the detection and prevalence estimation of specific conditions, electronic health record databases can act as a generalized population health surveillance system, giving insight into previously unmonitored diseases. For instance, Melamed et al showed the utility of EHRs to link diseases to seasonal trends [16]. Other seasonal detection methods using EHR data have been used to model seasonal influenza outbreaks, seasonal blood pressure controls, and seasonal effects on early child development [17][18][19].…”
Section: The Ehr As a Generalizable Population Health Surveillance Plmentioning
confidence: 99%